A new synthesis of 2,8-disubstituted pyrazolo[4,3-e][1,2,4]triazolo[1,5-c]pyrimidines - Dolzhenko, Anton; Pastorin, G.; Dolzhenko, A.; Chui, W. (Elsevier Science Limted, 2009)
A practical synthesis of pyrazolo[4,3-e][1,2,4]triazolo[1,5-c]pyrimidines, which are key intermediates inthe preparation of adenosine receptor antagonists, is developed. The method allows introduction of avariety of aryl substituents at position 2 of the pyrazolo[4,3-e][1,2,4]triazolo[1,5-c]pyrimidine systemvia cyclocondensation of 5-amino-4-iminopyrazolo[3,4-d]pyrimidine with benzaldehydes accompaniedwith oxidation by iodobenzene diacetate. Some unexpected reactions are observed and the structuresof the products are confirmed using NMR spectroscopy and X-ray crystallography.